Concentração sérica de sulfato de magnésio em gestantes com pré-eclâmpsia, submetidas aos esquemas de Zuspan e de Sibai - Batista, Fernanda Régnier Gaiotto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objectives: To compare magnesium sulphate levels in pregnant women diagnosed with imminent eclampsia or eclampsia and the amount of women who reached therapeutic levels when receiving intravenous magnesium sulphate regimens proposed by Zuspan and Sibai. Subjects and Methods: A prospective quasi-randomized clinical trial was conducted, which included 38 hypertensive pregnant women receiving clinical care in a university center for treatment of impending eclampsia or eclampsia. Patients were stratified according to the magnesium sulfate regimen that they were receiving in: Zuspan regimen group (20 patients) and Sibai regimen group (18 patients). Serum magnesium levels were measured at 9 time points: prior to treatment, 15', 30', 60 ', 90', 2 hours, 4 hours, 12 hours and 24 hours after treatment. For all analyzes, a significance level of 95% (p <0.05) was used. Results: The mean serum magnesium level at the Sibai regimen group was significantly higher when compared to the Zuspan regimen group at all times listed. Only in the Sibai regimen group, the mean serum level reached magnesium therapeutic values, however only in three time points (15 ', 12 hours and 24 hours). In the Sibai regimen group, a greater number of women reached the therapeutic magnesium sulfate level, which was significant the 30 minutes, 60 minutes, 2 hours, 4 hours and 12 hours dosages when compared to the Zuspan regimen group. Conclusion: Sibai regimen group maintained a higher serum level of magnesium when compared to the Zuspan regimen group and a greater number of women who have reached therapeutic levels of magnesium sulphate considered in the literature

Objetivo: Determinar a concentração sérica do íon magnésio, em gestantes com diagnóstico de eclâmpsia iminente ou eclâmpsia e comparar a proporção de mulheres que alcançaram concentração terapêutica, submetidas aos esquemas de sulfato de magnésio proposto por Zuspan e por Sibai. Sujeitos e métodos: Foi realizado estudo prospectivo, tipo ensaio clínico quasi-randomizado, no qual foram incluídas 38 gestantes hipertensas, que receberem assistência clínica para tratamento de eclâmpsia iminente ou de eclâmpsia. As gestantes foram estratificadas segundo o esquema de sulfato de magnésio que receberam em: grupo esquema de Zuspan (20 pacientes) e grupo esquema de Sibai (18 pacientes). Realizou-se dosagem sérica do íon magnésio em nove momentos: antes do tratamento e após 15', 30', 60', 90', 2 horas, 4 horas, 12 horas e 24 horas de tratamento. Para todas as análises foi utilizado o nível de significância de 95% (p<0,05). Resultados: A média da concentração sérica do íon magnésio no grupo esquema de Sibai foi significativamente maior do que no grupo esquema de Zuspan em todos os momentos estudados. Apenas no grupo esquema de Sibai, as médias das concentrações séricas do íon magnésio alcançaram valores terapêuticos, entretanto em apenas três momentos (15', 12 horas, 24 horas). No grupo esquema de Sibai houve maior número de mulheres que atingiram concentração terapêutica do sulfato de magnésio, sendo significativo nos momentos 30min, 60min, 2 horas, 4 horas e 12 horas, quando comparado com o grupo esquema de Zuspan. Conclusão: Gestantes do grupo esquema de Sibai mantiveram maior concentração sérica do íon magnésio do que as do grupo esquema de Zuspan e maior número de mulheres que atingiram a concentração terapêutica do sulfato de magnésio indicada pela literatura
Keywords: Pré-eclâmpsia; Mulheres grávidas; Magnésio - Efeito fisiológico; Magnesium - Physiological effect